Single-cell transcriptome atlas of peripheral immune features to Omicron breakthrough infection under booster vaccination strategies - Zhang, Yuwei; Han, Shanshan; Sun, Qingshuai; Liu, Tao; Wen, Zixuan; Yao, Mingxiao; Zhang, Shu; Duan, Qing; Zhang, Xiaomei; Pang, Bo; Kou, Zengqiang; Jiang, Xiaolin (Frontiers in Immunology, 2025)
IntroductionThe high percentage of Omicron breakthrough infection in vaccinees is an emerging problem, of which we have a limited understanding of the phenomenon.MethodsWe performed single-cell transcriptome coupled with T-cell/B-cell receptor (TCR/BCR) sequencing in 15 peripheral blood mononuclear cell (PBMC) samples from Omicron infection and naïve with booster vaccination.ResultsWe found that after breakthrough infection, multiple cell clusters showed activation of the type I IFN pathway and widespread expression of Interferon-stimulated genes (ISGs); T and B lymphocytes exhibited antiviral and proinflammatory-related differentiation features with pseudo-time trajectories; and large TCR clonal expansions were concentrated in effector CD8 T cells, and clonal expansions of BCRs showed a preference for IGHV3. In addition, myeloid cells in the BA.5.2 breakthrough infection with the fourth dose of aerosolized Ad5-nCoV were characterized by enhanced proliferation, chemotactic migration, and antigen presentation.DiscussionCollectively, our study informs the comprehensive understandings of immune characterization for Omicron breakthrough infection, revealing the positive antiviral potential induced by booster doses of vaccine and the possible "trained immunity" phenomenon in the fourth dose of aerosolized Ad5-nCoV, providing a basis for the selection of vaccination strategies.